A single‐beam full‐space scanning leaky‐wave antenna with high‐efficiency based on spoof surface plasmon polaritons. Issue 9 (6th June 2022) - Jiang, Huan; Cao, Xiangyu; Jidi, Liaori; Yang, Huanhuan; Gao, Jun
Abstract: A single‐beam full‐space scanning leaky‐wave antenna with high‐efficiency based on spoof surface plasmon polaritons (SSPPs) is presented in this paper. An array of circular patches is placed periodically around the SSPPs waveguide to couple the electromagnetic wave and radiate to the free space. The antenna has been simulated, manufactured and tested, and the results are consistent. The simulated results show that the antenna can keep a high radiation efficiency (the average efficiency can reach 87.4%) while ensuring the excellent characteristic of single‐beam scanning from backfire to endfire (180°) continuously within the operation bandwidth of 6.3–9.1 GHz (for |S11 | < −10dB). The simulation results demonstrate that the gain of the antenna can reach 11.0 dBi at backfire and 13.2 dBi at endfire, respectively. The antenna with full‐space scanning capability and high‐efficiency has great application value in wireless communication systems.